RELATIONSHIP BETWEEN VERTICAL CLASSIFICATION OF MAXILLARY THIRD MOLAR ROOTS AND MAXILLARY SINUS WITH AGE USING CBCT - Mutiara Sukma Suntana; Fadilah; Khairunnisa (Fakultas Kedokteran Gigi Unjani, 2026)
The maxillary third molar is one of the posterior teeth of the upper jaw that is in proximity to the maxillary sinus. This position can cause complications during third molar extraction. Cone Beam Computed Tomography (CBCT) is an imaging method that can see the vertical relationship between the tooth root and the maxillary sinus in more detail. The study used a cross-sectional method with sampling using a purposive sampling method. The population in this study was CBCT radiograph data of patients aged 20-50 years. 41 patient data were obtained, with 37 on the right side and 38 on the left side. The relationship between the tooth root and the maxillary sinus was seen in the coronal plane, and a vertical classification was carried out on the position of the tooth root. Spearman correlation analysis with a 95% confidence level obtained a correlation coefficient of -0.175 for the right third molar and -0.196. The significance value of p obtained was 0.301 for the maxillary right third molar and 0.238 for the maxillary left third molar, with a test value of p>0.05. There is no relationship between the vertical classification of the maxillary third molar root and the maxillary sinus in patients aged 20-50 years. DOI : 10.54052/jhds.v5n3.p331-338